Role of insulin-like growth factor, pro-inflammatory and anti-inflammatory cytokines, transcription factors and adipokines in development of hepatocellular carcinoma in metabolic syndrome - Smirnova, Olga V.; Gershkoron, F. A. (Medical Immunology Russia, 2022)
Conflicting data on the role of the metabolic syndrome (MS) in the development of hepatocellular carcinoma (HCC) require studies on the influence of molecular factors that are important in the development of HCC in MS, which was the goal of our review. Publications (scientific articles and reviews) over the past 10 years were studied and analyzed using the databases Web of Science, Scopus, PubMed, RSCI. The terms used for the search were “metabolic syndrome and non-alcoholic fatty liver disease”, “metabolic syndrome and non-alcoholic steatohepatitis”, “metabolic syndrome and hepatocellular carcinoma”. The total number of publications studied in all databases exceeded 570 units, while the review presents the most significant results at the present stage. Insulin resistance and obesity, through the development of a systemic chronic inflammatory state, lead to increased inflammation and fibrosis in the liver, which are prodromal signs of hepatocarcinogenesis, increase the production of insulin-like growth factor-1 and disrupt the regulation of the insulin-like growth factor pathway. People with HCC have been shown to overexpress IGF-2. IGF-binding proteins, due to the reduced bioavailability of free IGF-1 and IGF-2 in the circulation, are able to inhibit the growth of HCC. In MS, a pro-inflammatory state is detected, which is caused by the production of cytokines by adipocytes (IL-6, IL-8, IL-1β, tumor necrosis factor α (TNFα), VEGF and chemokine ligands 2 and 5), which recruit immune cells, promoting angiogenesis and enhancing chronic inflammation. Transcription factors (PPAR) are involved in hepatocarcinogenesis, the significance of different factors is not fully understood. Leptin has a positive prognostic value in HCC, improving overall survival, and visfatin has a negative effect on hepatocarcinogenesis. Activation of PAI-1 inhibits the progression of HCC through PPARγ stimulation. Adiponectin may be a prognostic marker in HCC, with a lower serum concentration positively correlated with worse prognosis.
CRIS-Team Scopus Importer:2023-04-20
Keywords: adipokines; cytokines; hepatocellular carcinoma; metabolic syndrome; non-alcoholic fatty liver disease; transcription factors